Feasibility of HCV micro-elimination: HCV test and treatment in two harm reduction services in Milan. (30th September 2020) - Mazzilli, S; Sebastiani, T; Casigliani, V; Cocca, G; Stemat, A; Nicola, C; Selva, P; Catani, C; Tavosci, L; Ranieri, R
Abstract: Background: Most of Harm Reduction Service (HRS) users represent a crucial high-risk population for blood borne infections, including HCV. With the advent of new direct antiviral agents (DAAs), HCV micro-elimination in this setting has become feasible. We evaluated HCV treatment cascade in two HRSs located in Milan. Methods: We collected data on demographics, substance abuse history, HIV prevalence, HCV prevalence, testing and treatment on all register HRS users on 1 January 2019. Data collection was closed on 1 January 2020. Results: A total of 881 HRS users (732M, 149F) were included (median age: 45). The majority was addicted to heroin 67.5% (595), 24.1%(212) to cocaine, 5.3%(47) to THC and 3.1%(27) to other substances. The 28.0%(247/881) reported current or prior judiciary problems, 168/881(19.1%) were under psychiatric treatment. HCV serological screening (HCVAb) was performed for 587/881(66.7%), 113/881(12.8%) were in process, 2/881(0.2%) refused, 179/881(20.3%) were not HRS user anymore. 364/587(62%) resulted HCVAb positive, of whom 288(79.1%) were tested for HCV RNA. Among them 123/324(37.9%) were positive, 165/324(50.9%) were negative. Among HCVAb positive, 116/364(31.9%) were tested for HIV and 92(79.3%) resulted HIV positive. Among HCV RNA positive 92/123(74.8%) were initiated on DAAs treatment. Compliance to treatment was high; one treatment failure was registered. Individuals tested for HCV and HCVAb positive people had an average age significantly higher than the individuals not tested and HCVAb negative people (p < 0.001). Heroin user had a higher likelihood of being tested both for HCVAb and for HCV RNA and of being positive to the HCVAb test (p < 0.001). Conclusions: Our study demonstrate that it is feasible to achieve good efficacy and compliance for HCV treatment among people who use drugs when decentralising treatment to HRS. To achieve the viral hepatitis elimination agenda goals, HRS-based model of treatment provision needs to be implemented at larger scale. Key messages: Decentralising HCV test and treatment to harm reduction services is an effective strategy to achieve HCV micro-elimination among people who use drugs. Young people and people who are addicted to other substance than heroin resulted more difficult to link to HCV care through the harm reduction services. They require tailored intervention.